Development and usability testing of a patient digital twin for critical care education: a mixed methods study - Rovati, Lucrezia; Gary, Phillip J.; Cubro, Edin; Dong, Yue; Kilickaya, Oguz; Schulte, Phillip J.; Zhong, Xiang; Wörster, Malin; Kelm, Diana J.; Gajic, Ognjen; Niven, Alexander S.; Lal, Amos (Frontiers in Medicine, 2024)
Background Digital twins are computerized patient replicas that allow clinical interventions testing in silico to minimize preventable patient harm. Our group has developed a novel application software utilizing a digital twin patient model based on electronic health record (EHR) variables to simulate clinical trajectories during the initial 6 h of critical illness. This study aimed to assess the usability, workload, and acceptance of the digital twin application as an educational tool in critical care. Methods A mixed methods study was conducted during seven user testing sessions of the digital twin application with thirty-five first-year internal medicine residents. Qualitative data were collected using a think-aloud and semi-structured interview format, while quantitative measurements included the System Usability Scale (SUS), NASA Task Load Index (NASA-TLX), and a short survey. Results Median SUS scores and NASA-TLX were 70 (IQR 62.5–82.5) and 29.2 (IQR 22.5–34.2), consistent with good software usability and low to moderate workload, respectively. Residents expressed interest in using the digital twin application for ICU rotations and identified five themes for software improvement: clinical fidelity, interface organization, learning experience, serious gaming, and implementation strategies. Conclusion A digital twin application based on EHR clinical variables showed good usability and high acceptance for critical care education.